PERAN SISTEM INTELIJENSIA BISNIS DALAM MANAJEMEN PENGELOLAAN PELANGGAN DAN MUTU UNTUK AGROINDUSTRI SUSU SKALA USAHA MENENGAH - Rina Fitriana, Eriyatno Taufik Djatna dan B.S. Kusmuljono TIP (Jurnal Teknologi Industri Pertanian, 2012)
Business intelligence systems participate to deliver an accurate and useful information to appropriate decision makers within the necessary timeframe to support an effective decision making in dairy agro- industry. The objective of this study was to determine the role of business intelligence systems to support customer relationship management and quality in dairy-agro industry medium enterprise. The combine methods to develop this research included Unified Modeling Language (UML), Fuzzy, Failure Mode Effect Analysis (FMEA), Cube, On Line Analytical Processing (OLAP), Extract, Transform, Loading (ETL) and Data warehouse. Data warehouse model is supported by ETL process. Business Intelligence Model is an integration of Cube, Data warehouse Model and Fuzzy system and it helps for a fast and efficient transaction in the system. The design consisted of quality and CRM (Customer Relationship Management) sub model. The Role of In Quality Sub Model based on Fuzzy, FMEA, the highest Fuzzy Risk Priority Number (FRPN) was 692 with type of failure, sum of Total Plate Control, bigger than 1 million/mL. The CRM (Customer Relationship Management) Model with RFM (Recency Frequency Monetory) and Customer Life Value (CLV) methods with OLAP Cube, the highest rank CLV for dairy processing industry to get potential customer was at PT FFI. The integration quality and CRM models into BI System would make it quickly anticipate, adapt, and react to the changing business conditions.   Keywords: Business Intelligence (BI), Unified Modelling Language (UML), OLAP, cube